Inhibitory effect of quercetin on titanium particle induced endoplasmic reticulum stress related apoptosis and in vivo osteolysis. Issue 4 (14th August 2017) - Zhang, Laibo; Tian, Zhoubin; Li, Wei; Wang, Xianquan; Man, Zhentao; Sun, Shui
Abstract : Wear particle induced periprosthetic osteolysis is the main cause of aseptic loosening of orthopedic implants. The aim of the present study is to determine the protective effect of quercetin (QUE) against titanium (Ti) particle induced endoplasmic reticulum stress (ERS) related apoptosis and osteolysis. In the present study, RAW264.7 cells were pretreated with different concentrations (40, 80, and 160 μmol/l) of QUE for 30 min and then treated with Ti particle (5 mg/ml) for 24 h. Cell viability and apoptosis were determined using MTT assay and Annexin V-FITC Apoptosis Detection Kit, respectively. Protein and mRNA expressions of ERS-related genes were examined by Western blot and real-time PCR, respectively. The release of inflammatory cytokines was detected by ELISA. Then, a mouse calvarial osteolysis model was established. Histological sections of calvaria were stained with Hematoxylin-Eosin (H&E) or tartrate-resistant acid phosphatase (TRAP). The results showed that Ti particle reduced cell viability and induced apoptosis in RAW264.7 macrophages. The cytotoxic effects of Ti particle were dramatically inhibited by QUE pretreatment. Interestingly, we found that QUE also significantly reduced Ti particle induced up-regulation of the expression levels of protein kinase RNA-like ER kinase (PERK), inositol-requiring enzyme-1 (IRE1), glucose-regulated protein (GRP78), CCAAT/enhancer-binding protein homologous protein (CHOP), caspase-12, and caspase-3 and enhanced the down-regulation of Bcl-2. In addition, QUE decreased Ti particle-induced inflammatory cytokines release from RAW264.7 cells. Moreover, treatment with QUE markedly decreased osteoclast number. In a mouse calvarial osteolysis model, QUE inhibited Ti particle induced osteolysis in vivo by inhibiting osteoclast formation and expressions of ERS-related genes. In conclusion, QUE can protect RAW264.7 cells from Ti particle induced ERS-related apoptosis and suppress calvarial osteolysis in vivo .